(3LGeY GdeYGQa hGdTQGFY hGdCMcGes - (3GdMSjfj, GdcGXej, oTnqHQ, GdeLdSj GdKGfj, YHO Gddg Hf eMeO QVG Bd THQ, J (B1242(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd RjGQI ChdjGFg ehLHI ddahR HKhGHg hQVGFg(B...(3CeG HYO gPG gh GdeLdO GdNGeS hgh eLdO GdeRGQ ef cJGH GdCMcGe(B...s
(3BNQgG (B:s
...(3Qhj Yf GdfHj U (B( (3ef ONd GdebGHQ abQC ShQI jS Naa Gddg Yfge jheFP hcGf dg HYOO ef ajgG MSfGJ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B2(3,U(B279s
(3GdPQjYI(B:(3L(B5(3,U(B50(3,Qbe(B281s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis